PEMANFAATAN BARANG BEKAS MENJADI KERAJINAN TANGAN GUNA MENINGKATKAN KREATIVITAS MASYARAKAT DESA PAOWAN - Indah Lestari Setiorini (Relawan Jurnal Indonesia, 2018)
The use of plastic in much kind of products has become unstoppable. It certainly impact on polluting the environment because plastic waste will require the immense period of time to degrade naturally. In order to reduce the plastic waste, Family welfare movement in Paowan has an initiave to train the employees to process plastic bottle waste into table lamp which functional and worth aesthetically. This research is the result of the outer implementation of PKM which use qualitative research method to analyze and qualify the research. Experimentative method is applied for the training and experiment program to make various derivative products made from plastic waste, by considering the design aspects such as: shape, size, function, and color. The results of the program acknowledges that the plastic waste combined with pipe,spon and box, with regards of design aspects becoming worth sellingvarious functional product. The real and practical sustainable social program such as PKM hopefully will strengthen the bond among education institution and the society